VD_FINDINFO HC / 2022 / 20 vom 13. Januar 2022 - VD Tribunal cantonal (2022)
CAS CLAIR, EXPULSION DE LOCATAIRE, VALEUR LITIGIEUSE | 257d al. 1 CO, 257d al. 2 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)